On Volterra Relatively Compact Perturbations of the \( \text{Laplace operator} \) - Biyarov, Bazarkan Nuroldinovich (Eurasian Mathematical Journal, 2014)
We formulate the result on existence of a relatively compact perturbation of the \( \text{Laplace operator} \) which possesses the Volterra property.